Down-regualtion of miR-106b induces epithelial-mesenchymal transition but suppresses metastatic colonization by targeting Prrx1 in colorectal cancer - Zheng, Lin (Int J Clin Exp Pathol, 2015)
Accumulating evidence identified that epithelial-mesenchymal transition (EMT) is acquired during progression to metastatic, but whether it is an absolute requirement is still controversial. MiR-106b has been confirmed to promote cancer cell proliferation; however few studies are available on its functions in EMT and metastasis in colorectal cancer (CRC). In this study, we found that knocking down miR-106b induced EMT conferring migratory and invasive properties. MiR-106b knockdown induced cytoskeletal reorganization through staining intracellular F-actin. The expression of Rho GTPases (Rac1 and Cdc42) and Tiam1 was significantly enforced after miR-106b down-regulation. However, miR-106b knocking down could suppress metastatic colonization in vivo. Correspondingly, over expression of miR-106b obtained an opposite effect. We identified Prrx1 was a direct target of miR-106b through using target prediction algorithms and dual-Luciferase reporter assay. Moreover, Moreover, we also found TGF-β1 could down-regulate miR-106b, and simultaneously miR-106b also influences the expression of TGF-β1, establishing a negative feedback loop to regulate the expression of Prrx1 together. Taken together, these findings demonstrated that miR-106b knockdown could induce EMT which conferring cells migratory and invasive properties but could not accomplish distant metastatic colonization efficiently.